DIAGNOSTIC AND CLASSIFICATION CRITERIA IN RHEUMATOLOGY: WHEN SHOULD THE CRITERIA BE USED AND HOW DO THEY DIFFER? - Yu. V. Muravyev (Научно-практическая ревматология)
There are virtually no diagnostic tests that can diagnose diseases of the musculoskeletal system and connective tissue with 100% sensitivity and 100% specificity, which was the reason for making both diagnostic and classification criteria to help practitioners and investigators. The application of these criteria is discussed in the article.